Economic Contribution and Infrastructure as Mediators of Tourism-Led Development in Sudurpaschim, Nepal - Chataut, Ram Kumar; Bisht, Nandan Singh; Saud, Hari Singh (Far Western Review, 2025)
This study examined the role of the tourism industry in enhancing economic development in Sudurpaschim Province, Nepal, focusing on the mediating effects of economic contribution and infrastructure development. This study utilized a cross sectional approach, gathering 657 valid responses from individuals involved in tourism activities. Descriptive data were analyzed using SPSS 26, while inferential relationships were tested using SmartPLS 4 through structural equation modeling (SEM). The results show that tourism significantly impacted economic contributions, infrastructure development, and economic development. The mediation results of economic contribution and infrastructure development showed partial mediation, with VAF values of 28.077% for economic contribution and 35.58% for infrastructure development. The HTMT and Fornell–Larcker criteria verified the reliability and validity of the model. The findings suggest that tourism directly and indirectly contributes to economic development by strengthening infrastructure and increasing economic activity, thus offering valuable implications for regional development strategies. The parallel mediation model verified partial mediation, tourism influence entirely transmitted through its impact on economic and infrastructure improvements. The findings suggest that destination managers should implement data-driven segmentation strategies aimed at age groups and nationalities that demonstrate the highest levels of engagement.